2003
DOI: 10.1111/j.1945-5100.2003.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind and other gases in the regoliths of the Pesyanoe parent object and the moon

Abstract: We report new data from Pesyanoe-90,1 (dark lithology) on the isotopic signature of solar wind (SW) Xe as recorded in this enstatite achondrite which represents a soil-breccia of an asteroidal regolith. The low temperature (≤800°C) steps define the Pesyanoe-S xenon component, which is isotopically consistent with SW Xe reported for the lunar regolith. This implies that the SW Xe isotopic signature was the same at two distinct solar system locations and, importantly, also at different times of solar irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Reported ratios 86 Kr/ 84 Kr = 0.303 ± 0.001 and 129 Xe/ 132 Xe = 1.06 ± 0.01, at this time the only values available from Genesis, are consistent with solar data as observed in early etch steps in lunar ilmenite samples (Wieler and Baur, 1994). Martian interior samples (SNC meteorites) also contain a solar type Xe-S component (Ott, 1988;Mathew and Marti, 2001), while SW-implanted Xe components were observed in gas-rich meteorites like Pesyanoe (Marti, 1969;Mathew and Marti, 2003). Minor solar components were observed in 'subsolar' gases in E-chondrites (Crabb and Anders, 1981;Busemann et al, 2003).…”
Section: Stellar Synthesis Products In Heavy Elementssupporting
confidence: 62%
“…Reported ratios 86 Kr/ 84 Kr = 0.303 ± 0.001 and 129 Xe/ 132 Xe = 1.06 ± 0.01, at this time the only values available from Genesis, are consistent with solar data as observed in early etch steps in lunar ilmenite samples (Wieler and Baur, 1994). Martian interior samples (SNC meteorites) also contain a solar type Xe-S component (Ott, 1988;Mathew and Marti, 2001), while SW-implanted Xe components were observed in gas-rich meteorites like Pesyanoe (Marti, 1969;Mathew and Marti, 2003). Minor solar components were observed in 'subsolar' gases in E-chondrites (Crabb and Anders, 1981;Busemann et al, 2003).…”
Section: Stellar Synthesis Products In Heavy Elementssupporting
confidence: 62%
“…Estimated temperatures of the wire coil during troilite decomposition are <700 °C to 400 °C, as determined by the position within the external furnace. The Xe separation and clean-up procedures in the static-mode mass spectrometric analyses were reported earlier (Mathew and Marti 2003). The Xe mass discrimination was determined and sensitivities monitored by air standard pipettes, and uncertainties in the corrections were propagated in the data (Table 1).…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The relatively frequent occurrence of solar wind (SW) gases in aubrites (Lorenzetti et al, 2003), the discovery of unusual FeO-rich clasts of unknown origin in Pesyanoe (Ivanova et al, 2002;Mathew and Marti, 2003) and of chondritic inclusions in Cumberland Falls (CF) (Mason, 1962) are several reasons to believe that the grains of aubrites had different histories in the regolith of a parent body. Early work on exposure ages (Eberhardt et al, 1965) indicated a cluster of cosmic-ray exposure (CRE) ages near 40 Ma, but such a cluster has been questioned in recent more comprehensive studies (Lorenzetti et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Large variations of 21 Ne c between the light and dark phases studied by Mü ller and Zähringer (1966) are inconsistent with shielding effects during space irradiation and generate discrepancies in CRE ages (Lorenzetti et al, 2003), but may represent a record of preirradiation of the regolith before compaction into the meteorite. Furthermore, Xe and N isotopic data in the dark portion of the Pesyanoe meteorite suggested the possibility of evolutionary processes before compaction of the meteoritic matter (Mathew and Marti, 2003).…”
Section: Introductionmentioning
confidence: 99%